Line scan-based rapid magnetic resonance imaging of repetitive motion - Hankyeol Lee (Nature Portfolio, 2021)
Abstract Two-dimensional (2D) line scan-based dynamic magnetic resonance imaging (MRI) is examined as a means to capture the interior of objects under repetitive motion with high spatiotemporal resolutions. The method was demonstrated in a 9.4-T animal MRI scanner where line-by-line segmented k-space acquisition enabled recording movements of an agarose phantom and quail eggs in different conditions—raw and cooked. A custom MR-compatible actuator which utilized the Lorentz force on its wire loops in the scanner’s main magnetic field effectively induced the required periodic movements of the objects inside the magnet. The line-by-line k-space segmentation was achieved by acquiring a single k-space line for every frame in a motion period before acquisition of another line with a different phase-encode gradient in the succeeding motion period. The reconstructed time-course images accurately represented the objects’ displacements with temporal resolutions up to 5.5 ms. The proposed method can drastically increase the temporal resolution of MRI for imaging rapid periodic motion of objects while preserving adequate spatial resolution for internal details when their movements are driven by a reliable motion-inducing mechanism.